Arabidopsis: An Adequate Model for Dicot Root Systems? - Zobel, Richard W. (Frontiers in Plant Science, 2016)
The Arabidopsis root system is frequently considered to have only three classes of root: primary, lateral, and adventitious. Research with other plant species has suggested up to 8 different developmental/functional classes of root for a given plant root system. If Arabidopsis has only three classes of root, it may not be an adequate model for eudicot plant root systems. Recent research, however, can be interpreted to suggest that pre-flowering Arabidopsis does have at least five (5) of these classes of root. This then suggests that Arabidopsis root research can be considered an adequate model for eudicot plant root systems.